Ontological–Metaphysical Hatred in Existential Crisis and Modern Conflict Transformation - Welem Novi Watunglawar; Mochamad Ziaul Haq (FOCUS, 2026)
This study aims to construct an ontological–metaphysical understanding of hatred as an existential wound of modern humanity and to reconstruct John Galtung’s ABC conflict model (Attitude–Behavior–Contradiction) through a hermeneutic phenomenological approach. This study is important because previous studies on hatred have primarily understood it as a psychological, moral, or socio-political phenomenon. Consequently, those studies have not adequately explored the ontological and metaphysical roots that generate hatred in modern life. This study employs a qualitative–interpretive approach grounded in hermeneutic phenomenology. The research data derive from philosophical, metaphysical, and conflict studies texts, which the study analyzes through reflective, interpretive, and dialogical readings of the thoughts of Martin Heidegger, Gabriel Marcel, Søren Kierkegaard, Frithjof Schuon, Seyyed Hossein Nasr, Meister Eckhart, and John Galtung. The findings demonstrate that hatred constitutes a manifestation of the fragmentation of consciousness, ego domination, and humanity’s disconnection from the wholeness and sacredness of reality. Hatred operates simultaneously at the levels of existential attitude, social behavior, and structural contradiction, thereby revealing that modern social conflict reflects a crisis of human existence itself. This study argues that sustainable conflict transformation requires the ontological restoration of human beings through relational openness, spiritual awareness, and the recovery of the sacred dimension of life. The implications of this study expand conflict and peace studies from a structural approach toward an ontological–metaphysical perspective. The originality of this study lies in its integration of phenomenology, spiritual metaphysics, and conflict theory in interpreting the essence of hatred as an existential wound of modern humanity.